Factors associated with watery diarrhoea diseases in under-five children in Chakari Mine of Sanyati District in Mashonaland West, Zimbabwe .September 2011. - George, Kambondo; Chadambuka, E.; Maxwell, Mhlanga; Ndaimani, Augustine (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Globally, there are about 3.2 million deaths worldwide in children under 5years from diarrhoea every year (WHO, 2010). Child mortality and morbidity mostly resultsfrom contaminated food and water sources. Reported attack rates in developing countriesrange from 1 to 12 episodes per child per year. Kadoma District before it was split onceexperienced outbreak of diarrhoea in 2007 where 34 children under five years died. Chakarimine area experienced an increase of watery diarrhoea cases since week 26 from 6% to 17%by week 39 of September 2011. The increase was noticed on the 6th of September 2011 ofwhich 74% of the cases were Children under the age of 5 years presenting with waterydiarrhoea, fever and some with vomiting. We set out to describe the outbreak and identifyrisk factors and institute prevention and control measures. Methodology: An unmatched 1:1case control was carried out. A case was any child under five years of age who presentedwith diarrhoea, with or without vomiting and other symptoms from the 6th of September 2011and has been resident in Chakari mine for two weeks prior to onset of the symptoms. Adiarrhoea case was defined as having passed three or more loose stools within 24 hours.Controls were any child who did not develop diarrhoea from the 6th of September up to theday of the interview, and has been a resident neighbour of Chakari mine for the previous twoweeks. An interviewer administered questionnaire was used for data collection. Checklist forresources was used. Multivariate analysis for risk factors was done using EPI INFO V 3.5.3statistical package. Results: A total of (76) case caregivers and (76) control caregivers wereinterviewed. Cold Sadza and cold porridge were statistically significant risk factors whichwere associated with contracting watery diarrhoea with Odds Ratio [13(95%CI 2.3, 71.7)p=0.00034] and [OR, 28.7(95% CI 2.2, 362.7)p=0.0096] respectively. Cold vegetables wereprotective from contracting diarrhoea with Odds Ratio [0.1(95% CI 0.01, 0.96) p=0.05].Washing of hands in one bowl at home was the only independent risk factor which wasstatistically significant associated with contracting diarrhoea in Chakari mine at adjustedOdds Ratio [11.4(95% CI 1.86,70.1) p=0.008]. Discussion and Conclusion: Cold Sadza andcold porridge was the major risk factors associated with contracting watery diarrhoea inChakari. The major finding indicated that the food was being contaminated by the practice ofwashing hands using the same bowl. The caregivers need health education on the importanceof hand washing before eating using the run to waste method. The water for Chakari mineneeds Chlorination to improve its quality.